2020
DOI: 10.1186/s10086-020-01872-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of incorporation of lignin as bio-polyol on the performance of rigid lightweight wood–polyurethane composite foams

Abstract: Density reduction has become a topical issue in wood composite materials for application in building and furniture. In this study, lightweight wood-polyurethane (W-PU) composite foams with the addition of 30 wt% wood particles were prepared. Industrial kraft lignin was used as bio-polyol to substitute partial petroleum-based diethylene glycol (DEG) to synthesize rigid W-PU foams. The effect of varying lignin contents (5, 10, 15 and 20 wt% based on DEG mass) on the reactivity, morphology, density, compressive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 39 publications
3
55
0
Order By: Relevance
“…Leszczyńska et al [ 51 ] showed that composites with nut shell were characterized by increased structure anisotropy and higher contents of the irregularly shaped pores than those of the reference sample. Lu et al [ 52 ] investigated PUR samples with up to a 20 wt% volume of wood or lignin. The usage of each filler resulted in the formation of poorer cellular structures, with large numbers of open cells, affecting the final properties of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…Leszczyńska et al [ 51 ] showed that composites with nut shell were characterized by increased structure anisotropy and higher contents of the irregularly shaped pores than those of the reference sample. Lu et al [ 52 ] investigated PUR samples with up to a 20 wt% volume of wood or lignin. The usage of each filler resulted in the formation of poorer cellular structures, with large numbers of open cells, affecting the final properties of the composite.…”
Section: Resultsmentioning
confidence: 99%
“…This might be due to the intensified decomposition of urethane bonds and decomposition of soft segments, i.e., polyols [ 85 ]. The formulations with high NCO:OH molar ratios showed T max3 at a temperature over 450 °C, which referred to the degradation of hard segments, such as pMDI and aromatic lignin moieties [ 86 ]. The thermal stability of cured PU adhesives was improved considerably by increasing the NCO:OH molar ratio in both CLW- or PLW-based formulations.…”
Section: Resultsmentioning
confidence: 99%
“…The intensities of FT-IR peaks corresponding to C-O stretch (1150 cm –1 , H units), C-O stretch (1263 cm –1 , G units), and syringyl C-O stretch (1360 cm –1 ) are significantly stronger than those of the original lignin. 39 , 40 Furthermore, the strong peak around 1718 cm –1 indicated a band of carboxyl stretching vibrations, 41 indicating that modified lignin contains carboxyl functional groups.…”
Section: Resultsmentioning
confidence: 99%